2021
DOI: 10.1039/d1ob01610e
|View full text |Cite
|
Sign up to set email alerts
|

Three-component synthesis, utilization and biological activity of phosphinoyl-functionalized isoindolinones

Abstract: A new method for the synthesis of 3-oxoisoindolin-1-ylphosphine oxides bearing same or different substituents on the phosphorus atom is described. The one-pot three-component reaction of 2-formylbenzoic acid, primary amines and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[54][55][56][57][58][59][60][61] In our research work, the three-component condensation of FBA, butyl-, cyclohexyl-, benzylamine or aniline and diphenylphosphine oxide was studied. 62 An efficient method was elaborated by us, where complete conversion was obtained in the absence of any catalyst, at room temperature, after short reaction times (10-20 min) in acetonitrile. The condensation was extended to various secondary phosphine oxides, such as bis(p-tolyl)-, bis(3,5-dimethylphenyl)-, bis(2-naphthyl)-or dibenzylphosphine oxides (Scheme 2).…”
Section: Synthesis Of (Oxoisoindolin-1-yl) Phosphine Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56][57][58][59][60][61] In our research work, the three-component condensation of FBA, butyl-, cyclohexyl-, benzylamine or aniline and diphenylphosphine oxide was studied. 62 An efficient method was elaborated by us, where complete conversion was obtained in the absence of any catalyst, at room temperature, after short reaction times (10-20 min) in acetonitrile. The condensation was extended to various secondary phosphine oxides, such as bis(p-tolyl)-, bis(3,5-dimethylphenyl)-, bis(2-naphthyl)-or dibenzylphosphine oxides (Scheme 2).…”
Section: Synthesis Of (Oxoisoindolin-1-yl) Phosphine Oxidesmentioning
confidence: 99%
“…Among (3-oxo-2,3-dihydro-2H-isoindol-1-yl)phosphine oxides 23-34, derivatives containing 3,5-dimethylphenyl-or naphthyl groups on the phosphorus atom showed activity. 62 The N-butyl and N-benzyl bis(3,5-dimethylphenyl)…”
Section: Biological Activity Investigationsmentioning
confidence: 99%
“…In these cases, an increased temperature of 60 °C in a MW reactor was necessary to form the corresponding benzo[de]isoquinolin-1-one-3-phosphine oxides (18)(19)(20) in good yields. Finally, the three-component reaction of 1,8-naphthalaldehydic acid with the secondary phosphine oxides mentioned above was also carried out using a chiral primary amine, DL-1-phenylethylamine.…”
Section: Synthesis Of Benzo[de]isoquinolin-1-one-3-phosphine Oxidesmentioning
confidence: 99%
“…Finally, the in vitro cytotoxicity on the MV-411 cell line was investigated, and it was found that all of the compounds showed moderate or good activity against these cells. The most active compounds were bis(3,5-dimethylphenyl) (2-benzyl-3-oxo-2,3-dihydro-1H-benzo[de]isoquinolin-1-yl)phosphine oxide (17) and bis(p-tolyl)-( 19) as well as bis(3,5-dimethylphenyl) [2-(3dimethylamino-propyl)-3-oxo-2,3-dihydro-1H-benzo[de]isoquinolin-1-yl)phosphine oxide (20).…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
See 1 more Smart Citation